HUBUNGAN INTENSITAS MEROKOK DAN KADAR C-REACTIVE PROTEIN TERHADAP PENYAKIT PARU OBSTRUKTIF KRONIS (PPOK) - Swastikanti, Ruth Aktrisari; Pakpahan, Edwin A.; Silangit, Thomas (Jurnal Kedokteran Methodist, 2021)
Background: Chronic obstructive pulmonary disease (COPD) is a specific non-inflammatory disease, which occurs in the airways, parenchyma of lung, and pulmonary vessels. The processes leading to the development of COPD are heterogeneous. CRP is the result of the synthesis of acute phase proteins mainly by hepatocytes as response to tissue damage or inflammation. It is accepted where CRP-levels are associated with the existemce of airflow interference and are also associated with disease severity, exercise capacity, quality of life,  response to treatment and mortality. Methods: This study is a study using the literature study method or literature review. Data obtained from secondary data using documentation techniques. Data documentation is carried out based on journals related to research variables. Results: Based on a literature review study, there are 9 journals related to the relationship between smoking intensity and C-Reactive Protein levels to chronic obstructive pulmonary disease. Conclusion: After conducting a literature review process, it was found that there was a relationship between smoking intensity and C-reactive protein levels on chronic obstructive pulmonary disease (COPD).